Evolutionary Relationship and Structural Analysis of Blast Resistance Associated Novel Osvwa36 and Osvwa37 Genes in Cultivated and Wild Species of Rice - Karkute, Suhas Gorakh; Sevanthi, Amitha Mithra; Solanke, Amolkumar U. (International Journal of Bio-resource and Stress Management, 2023)
Rice blast is a dreadful disease that causes enormous losses in rice production worldwide. To develop blast resistant rice cultivars, it is necessary to identify resistance and defence regulator genes and the underlying mechanism of resistance. A novel von Willebrand factor domain A containing genes OsvWA36 and OsvWA37 in Tetep cultivar of rice regulate response to Magnaporthe oryzae infection and provides significant resistance. Owing to the important role of these genes, their evolutionary relationship has been studied in cultivated and wild species of rice. There is significant diversity in the protein sequence of these genes among the relative wild rice species. The size of OsvWA36 protein varies from 501 aa to 698 aa whereas size of OsvWA37 protein varies from 295 aa to 1004 aa. The, OsvWA36 gene is evolutionarily more conserved than OsvWA37 among the different rice species indicating its critical role. Besides the global variation in protein sequence, the region of vWA domain is highly conserved among all the species. Interestingly, both the genes in Oryza barthii are fused to form a single gene encoding a large protein that indicates their origin in other species from a single gene. The good quality tertiary structures of both OsvWA36 and OsvWA37 proteins in cultivated germplasm cv. Tetep were also generated which can be utilized for protein structural and docking studies.